ANALISIS TEMUAN AUDIT BERDASARKAN LAPORAN HASIL PEMERIKSAAN (LHP) BPK DI PROVINSI SULAWESI TENGGARA TA 2018-2022 - Rika, Abdul Rachman (LPPM Universitas Putera Batam, 2025)
This study aims to analyze the audit findings of the Audit BPK that occurred in Southeast Sulawesi Province. The analysis carried out is generally carried out in four parts starting from the Analysis of Accounts Based on the Findings of the BPK Audit Report on the Regional Government Financial Report, then the frequency analysis of findings will be analyzed based on the Type of Regional Government Financial Report on the same account, conducting problem analysis of the findings accounts, and analyzing recurring findings in the accounts of the Regional Government Financial Report in Southeast Sulawesi Province for the 2018-2022 Budget Year. The study uses secondary data obtained from the Audit Report of the Audit Board of Indonesia in Southeast Sulawesi Province during the period 2018 to 2022. The type of research used is qualitative research with an analysis method using content analysis. The results of the study show that the pattern of findings occurs due to lack of supervision by each level in each Regional Apparatus Organization and non-compliance with laws and regulations carried out by government officials, and not all findings that occur more than once in the same account have indications of repeated findings, but the results of this study analysis show several accounts that have indications of repeated findings. Based on the frequency of findings based on the type of financial report, weaknesses in the internal control system and non-compliance with laws and regulations in the management of the Southeast Sulawesi Provincial Government Finance are still found, which are caused by weak internal control systems in each Regional Apparatus Organization, non-compliance with laws and regulations, the role of other parties that are not optimal, and incomplete follow-up.